Angioarchitecture and prognosis of pediatric intracranial pial arteriovenous fistula - Guilin Li; Jingwei Li; Xinglong Zhi; Lisong Bian; Fan Yang; Hongqi Zhang; Jiaxing Yu; Jian Ren; Zhenlong Ji (Stroke and Vascular Neurology, 2023)
Objective Pial arteriovenous fistulas (PAVFs) are rare and mostly observed in children. However, the overall angioarchitecture, clinical features, treatments and long-term prognosis for pediatric patients remain unclear.Methods Clinical data of consecutive 42 pediatric PAVFs were documented and analysed. According to the differences of age distribution and clinical features, they were split into a younger group (≤3 years old; 20 cases) and an older group (3–14 years old; 22 cases).Results Their mean age was 4.9±3.9 years, and the mean preoperative modified Rankin Scale (mRS) score was 1.64±1.57. Fourteen patients (33.3%) were asymptomatic, followed by epilepsy (21.4%), intracranial haemorrhage (16.7%), hydrocephalus (9.5%), developmental delay (7.1%), intermittent headache (7.1%) and congestive heart failure (4.8%). Annual bleeding rate and rebleeding rate before treatment reached 3.86% and 3.17%. Poor venous drainage including sinus dynamic obstruction (21 cases, 50.0%) and sinus occlusion (17 cases, 40.48%) were found with high frequency among these patients. Finally, 33 cases were cured (78.57%), and 4 cases faced surgery-related complications (9.52%). During 24–140 months’ follow-up, the mean mRS score reduced to 0.57±0.40. However, only 22 cases (52.38%) recovered to absolutely normal, and poor venous drainage was the risk factor for patients’ incomplete recovery (p=0.028, Exp(B)=14.692, 95% CI 1.346 to 160.392). Compared with the older group, younger group showed more chronic symptoms, more secondary pathological changes, more times treatment and worse prognosis (p=0.013, 0.002, 0.000 and 0.032, respectively).Conclusions Pediatric PAVF has different angioarchitectures, clinical features and prognoses in different age groups. Poor venous drainage is an important factor leading to poor prognosis, and it accounts for incomplete recovery in nearly half of patients.